Analisis Tingkat Emisi Co2-Eq Dan Potensi Energi Listrik Dari Landfill Gas TPA 2 Muara Fajar Kota Pekanbaru Dengan Pemodelan Landgem Version 3.02 (Landfill Gas Emissions Model) - Nurmaida, Betharia; Sasmita, Aryo; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The population growth of Pekanbaru City that increased in every year is the main factor of the increasing waste that enters the MSWD 2 Muara Fajar, Pekanbaru City. The garbage piled up in landfills will have a process named degradation to produce methane gas (CH4). This gas contributes to the global warming phenomenon but has the potential to be used as alternative energy. The purpose of this study to estimate the methane gas emissions from landfilling activities at MSWD 2 Muara Fajar with the LandGEM ver 3.02 software, and analyzes the potential energy that can be generated from methane gas. Based on the estimation results of LandGEM ver 3.02, total of methane gas emmisions from MSWD 2 Muara Fajar reached the peak in 2049 with values are 23.110 Mg/year or 34.630.000 m3/year. The total level of CO2-eq emissions from MSWD 2 Muara Fajar Pekanbaru City during the operation to closing (20182048) are 8,780,688 MgCO2-eq. The total daily electricity power that can be produce from the methane are 1,322,547.09 kWh which is supplied the daily electricity needs of 237,608 households in Pekanbaru City. Keywords: Municipal Solid Waste Disposal, methane, LandGEM, energy potential